Romans. A Commentary, Robert Jewett - du Toit, Andrie (Neotestamentica, 2008)
This massive Romans commentary represents 26 years of painstaking labour by an erudite scholar on one of the most influential but also most hotly debated books of the NT. One is immediately impressed by its reader-friendliness. Although somewhat heavy to handle, this book is a real delight to consult and read. Its layout and presentation is immediately clear, in contrast, for instance, to the Romans commentary of Käsemann where one almost needs a tracking device to locate a specific item. The language is lucid and precise. For the uninitiated, Greek texts are translated into English and, in addition to the customary indices, a handy glossary of rhetorical and exegetical terms is provided.